2021
DOI: 10.1017/s1047951121000627
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in children and adolescents with CHD: review from a measurement methodological perspective

Abstract: Aim: To compile a literature overview of physical activity in children with CHD and to critically evaluate the methodology used for physical activity assessment. Methods: A review of the literature was performed using PubMed to identify studies examining accelerometer and subjectively assessed physical activity in children and adolescents with CHD. Result: A total of 15 studies were included (6 studies using subjective measures and 9 articles using accelerometers for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Research by Voss and colleagues studied the Physical Activity Questionnaire for Children (PAQ-C) in children and adolescents with CHD and found the PAQ-C summary score was significantly correlated with total PA (counts per day), PA intensity, moderate-to-vigorous intensity PA (MVPA), vigorous intensity PA, and sedentary time measured with waist-worn, research grade ActiGraph accelerometer (24). Although self-report PA questionnaires can provide some estimates of PA, device-based assessments of PA present an objective and more accurate estimate of PA participation when compared to self-reported PA. A review by Skovdahl and colleagues of 15 studies that examined various methodologies in the assessment of PA in patients with CHD, the authors found wide variations self-reported PA when compared to healthy peers, but no between-group differences when PA is measured with wearable devices (25). The authors suggest methodological variation and limitations in self-report assessment may be responsible for these differences.…”
Section: Physical Activity and Fitness Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Voss and colleagues studied the Physical Activity Questionnaire for Children (PAQ-C) in children and adolescents with CHD and found the PAQ-C summary score was significantly correlated with total PA (counts per day), PA intensity, moderate-to-vigorous intensity PA (MVPA), vigorous intensity PA, and sedentary time measured with waist-worn, research grade ActiGraph accelerometer (24). Although self-report PA questionnaires can provide some estimates of PA, device-based assessments of PA present an objective and more accurate estimate of PA participation when compared to self-reported PA. A review by Skovdahl and colleagues of 15 studies that examined various methodologies in the assessment of PA in patients with CHD, the authors found wide variations self-reported PA when compared to healthy peers, but no between-group differences when PA is measured with wearable devices (25). The authors suggest methodological variation and limitations in self-report assessment may be responsible for these differences.…”
Section: Physical Activity and Fitness Assessmentmentioning
confidence: 99%
“…Short, sporadic, and high-intensity bouts of PA are difficult to quantify via recall questionnaires, and youth tend to over-estimate PA when self-reported on valid and reliable questionnaires (4,25). Device-based measures of PA allow clinicians and researchers to perform well-described analysis methods providing insights into specific patterns of PA, including weekly frequency, bout pattern, intensity metrics and daily timing (26)(27)(28).…”
Section: Physical Activity and Fitness Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cut-off points recommended by Phillips et al (30) will be used and are specific for GENEActiv wrist-worn accelerometers in children ranging between 6-19 (g/s) for light PA, 20-60 (g/s) for moderate PA, >60 (g/s) for vigorous PA, and anything less that 6 (g/s) is regarded as sedentary. An increased number of days and hours of wear time are recommended for higher precision and therefore participants' will be included in the data analysis if the wear time has been at least 16 hours/day for at least 4 days of the week (≥ 3 weekdays and ≥1 weekend day) (32).…”
Section: Physical Activity Assessmentmentioning
confidence: 99%